2018
DOI: 10.1002/psc.3092
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and purification of self‐assembling peptide‐oligonucleotide conjugates by solid‐phase peptide fragment condensation

Abstract: Peptide-oligonucleotide conjugates (POCs) are interesting molecules as they covalently combine 2 of the most important biomacromolecules. Sometimes, the synthesis of POCs involves unexpected difficulties; however, POCs with self-assembling propensity are even harder to synthesize and purify. Here, we show that solid-phase peptide fragment condensation combined with thiol-maleimide or copper-catalyzed azide-alkyne cycloaddition click chemistries is useful for the syntheses of self-assembling POCs. We describe g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Although in our previous reports solid-phase peptide fragment condensation was advantageous over other methods for the fabrication of self-assembling POCs, [18,26] liquid-phase fragment conjugation was exploited in this report because cyclizing the POCs while remaining on the solid support (controlled pore glass) was not feasible using the thiol-maleimide reaction and CuAAC. Namely, it was inevitable to cleave the DNAs off the solid support to expose the thiol group at the in the cyclization of other materials, [27][28] the HPLC retention time of CycPOC-1 (T R = 31.4 minutes) was different from that of LinPOC-1…”
Section: Resultsmentioning
confidence: 97%
“…Although in our previous reports solid-phase peptide fragment condensation was advantageous over other methods for the fabrication of self-assembling POCs, [18,26] liquid-phase fragment conjugation was exploited in this report because cyclizing the POCs while remaining on the solid support (controlled pore glass) was not feasible using the thiol-maleimide reaction and CuAAC. Namely, it was inevitable to cleave the DNAs off the solid support to expose the thiol group at the in the cyclization of other materials, [27][28] the HPLC retention time of CycPOC-1 (T R = 31.4 minutes) was different from that of LinPOC-1…”
Section: Resultsmentioning
confidence: 97%
“…In addition, 1,3-dipolar cycloaddition between alkynes and azides is intrinsically chemoselective, which allows for conjugation of the fragments without the need for any protecting groups. It was also found that, in contrast to the thiol-maleimide conjugation, when the solubility of the peptide strongly influences the reaction rate, the copper-catalyzed alkyne-azide cycloaddition proceeds well even with sparingly soluble peptides [ 311 ].…”
Section: Post-synthetic Conjugation Approachesmentioning
confidence: 99%
“…Alternatively, post-synthetic modification of oligonucleotides may be performed on the solid support outside of the synthesizer. In this case, one can perform the functionalization not only through phosphoramidite/H-phosphonate chemistry, but also by other approaches, including Michael addition [19], or Cu(I)-catalyzed azide-alkyne Huisgen cycloaddition (see, e.g., [19,20]).…”
Section: Introductionmentioning
confidence: 99%